Condition monitoring of reciprocating seal based on FBG sensors. (24th June 2016) - Zhao, Xiuxu; Zhang, Shuanshuan; Wen, Pengfei; Zhen, Wenhan; Ke, Wei
Abstract: The failure of hydraulic reciprocating seals will seriously affect the normal operation of hydraulic reciprocating machinery, so the potential fault condition monitoring of reciprocating seals is very important. However, it is extremely difficult because of the limitation of reciprocating motion and the structure constraints of seal groove. In this study, an approach using fiber Bragg grating (FBG) sensors is presented. Experimental results show that the contact strain changes of a reciprocating seal can be detected by FBG sensors in the operation process of the hydraulic cylinders. The failure condition of the reciprocating seal can be identified by wavelet packet energy entropy, and the center frequency of power spectrum analysis. It can provide an effective solution for the fault prevention and health management of reciprocating hydraulic rod seals.